2016
DOI: 10.1111/all.13070
|View full text |Cite
|
Sign up to set email alerts
|

Asthma outcomes improve with continuous positive airway pressure for obstructive sleep apnea

Abstract: BackgroundContinuous positive airway pressure (CPAP) in asthma patients with concomitant obstructive sleep apnea syndrome (OSAS) seems to have a favorable impact on asthma, but data are inconsistent due to methodological limitations of previous studies.MethodsProspective, multicenter study. We examined asthma outcomes after 6 months of CPAP in 99 adult asthma patients (mean age 57 years) with OSAS (respiratory disturbance index ≥20). Asthma control and quality of life were assessed with the Asthma Control Ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 43 publications
1
56
0
3
Order By: Relevance
“…Treatment of OSAS with CPAP improves asthma control . Short‐term CPAP treatment has been demonstrated to reduce airway hyperresponsiveness in asthma already after 7 days .…”
Section: Obstructive Sleep Apnoea Syndromementioning
confidence: 99%
“…Treatment of OSAS with CPAP improves asthma control . Short‐term CPAP treatment has been demonstrated to reduce airway hyperresponsiveness in asthma already after 7 days .…”
Section: Obstructive Sleep Apnoea Syndromementioning
confidence: 99%
“…Although the effect has not been studied in difficult asthma per se, CPAP treatment may improve symptom control, lung function, as well as decrease exacerbation rates [148] and airway hyperresponsiveness in asthma in general [149]. …”
Section: Management Of Severe Asthmamentioning
confidence: 99%
“…The AHI is significantly associated with the occurrence of severe asthma exacerbations (4). Researchers have found that long-term treatment of CPAP in patients with both asthma and obstructive sleep apnoea can decrease the asthma symptoms and improve asthma control and quality of life (9,10). Since evaluating OSA in patients with asthma has been included in the Guidelines for the Diagnosis and Management of Asthma (21), there is a need for clinical investigations of early and periodic detection of OSA among asthma populations.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic data showed that the prevalence of OSA among asthmatic populations ranges from 38% up to as high as 70% (7). There is growing evidence that continuous positive airway pressure (CPAP) in adults and adenotonsillectomy in children which are recommended as first line treatment of OSA can improve their asthma symptoms (8)(9)(10). Mild OSA in severe asthma patients is associated with increased proportion of neutrophils in sputum and changes in airway remodeling (11,12).…”
Section: Introductionmentioning
confidence: 99%